EFEKTIFITAS LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN REALITA DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMA NEGERI 1 AMBARAWA - ivana wafiq muafiqoh (MEDIKONS, 2021)
Abstract: The purpose of this study was to provide students with an understanding of the importance of learning motivation in SMA Negeri 1 Ambarawa. This type of research was quantitative in the form of a quasi-experimental design with a nonequivalent control group design. The population of this research is the students of class XI . Samples were taken using purposive sampling taken as many as 20 students. The data in this study were obtained through a research instrument in the form of a learning motivational psychology scale. The results of the increased research showed that the learning motivation of students before and after being given treatment with group counseling services with a reality counseling approach experienced an average increase of 17.8. Based on the calculation of the hypothesis test of the Peired simple t-test or t-test, with a significant level of =5% (0.005), the experimental group has a sig value. (2-tailed 0.000 < 0.05) where H0 is accepted, meaning that there is an effect of the treatment given to the experimental group. While the control group got a sign value of 0.046 > 0.05 where Ho was rejected, meaning that there was no effect on the control group. In conclusion, group counseling with a reality approach can increase students' learning motivation at SMA Negeri 1 Ambarawa. Based on the results of this study, the suggestion that can be conveyed is that group counseling services with a reality approach can be used as an alternative for BK teachers in providing services. Key Words: Group Counseling; Reality Approach; Motivation to learn